2022
DOI: 10.3389/fnut.2022.851761
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Profiles of Raw and Cooked Donkey Meat by Metabonomics and Lipidomics Assessment

Abstract: Heat cooking of meat gives it a specific taste and flavor which are favored by many consumers. While the characteristic taste components of chicken, duck, pig, and seafood have been studied, there is a lack of information about the molecular components that give donkey meat its unique taste. Here, the characterization profiles of raw donkey meat (RDM) and cooked donkey meat (CDM) meat by metabonomics and lipidomics. The results showed that a total of 186 metabolites belonging to 8 subclasses were identified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…2d). Finally, 116 differential metabolites with fold change ≥2 or ≤0.5, VIP > 1, and p < 0.05 were identified in our study according to previous reports [12][13][14][15] , and the result is displayed in the volcano plot (Supplementary Fig. 1).…”
Section: Resultsmentioning
confidence: 87%
“…2d). Finally, 116 differential metabolites with fold change ≥2 or ≤0.5, VIP > 1, and p < 0.05 were identified in our study according to previous reports [12][13][14][15] , and the result is displayed in the volcano plot (Supplementary Fig. 1).…”
Section: Resultsmentioning
confidence: 87%
“…For instance, a large number of VOCs, including aldehydes, ketones, alcohols, carboxylic acids, and esters, have been detected in mutton, with 4-methyl octanoic acid and 4-ethyl octanoic acid playing major roles in mutton smell ( 10 ); while aldehydes are the main VOCs in donkey meat, as revealed by solid-phase microextraction–gas chromatography–mass spectrometry (SPME–GC–MS), with hexanal the most abundant volatile flavor compound ( 3 , 11 ). Other SPME-GC–MS studies have shown that maltotriose, L-glutamate, and L-proline are the main contributors to the unique taste of donkey meat ( 12 ). GC–MS or gas chromatography–olfactometry–mass spectrometry (GC–O–MS) are commonly used to identify the VOCs in meat and meat products ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…These amino acids play vital roles in the synthesis of glutamine and alanine, which are released in excess during protein‐rich meals and post‐absorption periods [37]. Previous studies have established higher levels of serum Asp, Asn, and Glu as significant markers of amino acid deficiency in older adults with physical frailty and sarcopenia (PF&S) [38]. Asp, Asn, and Glu may cause disturbances in various muscle‐specific and interorgan processes that regulate the overall energy metabolism, cellular anabolic pathways, and nitrogen/glutamine homeostasis.…”
Section: Discussionmentioning
confidence: 99%